BRCA1 Polymorphisms and Breast Cancer Epidemiology in the Western New York Exposures and Breast Cancer (WEB) Study. Issue 5 (14th May 2013) - Ricks‐Santi, Luisel J.; Nie, Jing; Marian, Catalin; Ochs‐Balcom, Heather M.; Trevisan, Maurizio; Edge, Stephen B.; Freudenheim, Jo L.; Shields, Peter G.
ABSTRACT Results of studies for the association of BRCA1 genotypes and haplotypes with sporadic breast cancer have been inconsistent. Therefore, a candidate single nucleotide polymorphism (SNP) approach was used in a breast cancer case‐control study to explore genotypes and haplotypes that have the potential to affect protein functions or levels. In a breast cancer case‐control study, genotyping of BRCA1 polymorphisms Q356R, D693N, and E1038G was performed on 1, 005 cases and 1, 765 controls. Unconditional, polytomous logistic regression and χ2‐tests were used to examine the associations of breast cancer with genotypes and haplotypes. In addition, interactions between genotype and smoking, benign breast disease, family history of breast cancer, body mass index (BMI), alcohol consumption, and hormonal risk factors, hormone receptor status, and breast cancer pathology were calculated also using logistic regression and χ2. Although sporadic breast cancer was not associated with BRCA1 genotypes or haplotypes overall or by menopausal status, there was evidence of an interaction between the E1038G BRCA1 genotype, smoking, and BMI among premenopausal women (P for interaction = 0.01 and 0.045, respectively) and between E1038G and D693N BRCA1 genotypes and hormone therapy use among postmenopausal women (P for interaction = 0.01 and 0.02, respectively). There were no other associations found between BRCA1 genotypes and stage, histological grade, or nuclear grade. However, the D693N SNP was associated with the risk of triple negative breast cancer (odds ratio = 2.31 95% confidence interval 1.08–4.93). The BRCA1 variants studied may play a role in the etiology of triple negative breast cancer and may interact with environmental factors such as hormone therapy or smoking and increase sporadic breast cancer risk.